Determinants of RFID Adoption in Malaysia’s Healthcare Industry: Occupational Level as a Moderator - Zailani, Suhaiza; Iranmanesh, M.; Nikbin, D.; Beng, J.K.C. (Springer Verlag, 2015)
With today’s highly competitive market in the healthcare industry, Radio Frequency Identification (RFID) is a technology that can be applied by hospitals to improve operational efficiency and to gain a competitive advantage over their competitors. The purpose of this study is to investigate the factors that may effect RFID adoption in Malaysia’s healthcare industry. In addition, the moderating role of occupational level was tested. Data was collected from 223 managers as well as healthcare and supporting staffs. This data was analyzed using the partial least squares technique. The results show that perceived ease of use and usefulness, government policy, top management support, and security and privacy concerns have an effect on the intent to adopt RFID in hospitals. There is a wide gap between managers and healthcare staff in terms of the factors that influence RFID adoption. The results of this study will help decision makers as well as managers in the healthcare industry to better understand the determinants of RFID adoption. Additionally, it will assist in the process of RFID adoption, and therefore, spread the usage of RFID technology in more hospitals.